'If you prick me, do I not bleed?': Antisemitism, racism and group analysis —some thoughts. (September 2021) - Bacha, Claire; Einhorn, Sue; Lieberman, Sue
The Merchant of Venice contains some of the most powerful depictions of Jewish–Christian relations in an era when Christian antisemitism dominated European life. It is one of the most difficult plays for Jews to watch: not only for Shylock's torment at the treatment he is subjected to, particularly in the Christian characters' relentless contempt for him, but for the depiction of his gradual descent into violent revenge, as a result of which he himself is crushed. The revenge part of Shylock's speech is crucial. The anti-Semites in the play unconsciously fear their victim, especially after treating Shylock with cruelty and contempt. The racists then project hatred, consequently fearing that Shylock will hate them, that he will be filled with rage and seek a revenge even more cruel than that which has been perpetrated upon him. Shylock speaks the racist's fear and then wants to carry it out. In Shakespeare's play, Shylock becomes a justification for hatred. If we look at this as the unconscious of antisemitism, then Shakespeare is personifying this unconscious in the character of Shylock. Seen in this way, The Merchant of Venice is a dramatic depiction of the violent effects of antisemitism on the subjectivity and identity of both victims and perpetrators. We know that racism creates trauma. Sue Lieberman's work on transmitted trauma (Lieberman, 2015) and Earl Hopper's work on massification and aggregation both explored unprocessed trauma (Hopper, 2003). However, the permeating trauma of both racism and antisemitism has festered without being addressed adequately. Our purpose in this article is to begin to look at this disturbing truth. We will address the historical relationship between antisemitism and racism. We will make links to the development of psychoanalysis and group analysis. That Foulkes, himself was a victim of racism has always been present but largely unspoken. Unspoken, it has created blind spots, including our own racism.